Origin of Fairy Tales About Youngest Brother and Their Role in The Formation of English Fairy Tale Epos - Darmon Uraeva Saidakhmedovna; Nilufar Zokirova Hamidovna (Genius Journals, 2021)
The article provides information on the history of tales about youngest son and their place in English literature. There are also points of various scholars and their researches on the history of the fairy tales, its development and factors that served as the cause of their origin in the work. In addition, the sample named “The King of England and his Three Sons” by J.Jacob was analyzed using examples.
Keywords: Youngest Brother; Motif; Minority; Idealization